Advances in materials science and technology (AMST) : selected, peer reviewed papers from the National Symposium on Advances in Materials Science and Technology (AMST-2012), February 3-4, 2012, Ahmedabad, India - Joshi, Utpal S. (Diffusion and defect data. Solid state phenomena ;, 2014)
This special volume covers topics such as novel synthesis, processing and applications of advanced materials, micro and nano-structures, oxides and magnetic materials, nanomaterials, semiconductors, microwave dielectric, multiferroics, computational materials science, modeling and simulation of advanced materials and technology such as cryogenics and smart material for health care. The 54 papers examine matters in such areas as novel synthesis, processing and applications of advanced materials, microstructures and nanostructures, oxides and magnetic materials, nanomaterials, semiconductors, mi.